Describing a principles-based approach to developing and evaluating peer worker roles as peer support moves into mainstream mental health services. Issue 3 (12th June 2017) - Gillard, Steve; Foster, Rhiannon; Gibson, Sarah; Goldsmith, Lucy; Marks, Jacqueline; White, Sarah
Abstract : Purpose: Peer support is increasingly being introduced into mainstream mental health services internationally. The distinctiveness of peer support, compared to other mental health support, has been linked to values underpinning peer support. Evidence suggests that there are challenges to maintaining those values in the context of highly standardised organisational environments. The purpose of this paper is to describe a "principles-based" approach to developing and evaluating a new peer worker role in mental health services. Design/methodology/approach: A set of peer support values was generated through systematic review of research about one-to-one peer support, and a second set produced by a UK National Expert Panel of people sharing, leading or researching peer support from a lived experience perspective. Value sets were integrated by the research team – including researchers working from a lived experience perspective – to produce a principles framework for developing and evaluating new peer worker roles. Findings: Five principles referred in detail to: relationships based on shared lived experience; reciprocity and mutuality; validating experiential knowledge; leadership, choice and control; discovering strengths and making connections. Supporting the diversity of lived experience that people bring to peer support applied across principles. Research limitations/implications: The principles framework underpinned development of a handbook for a new peer worker role, and informed a fidelity index designed to measure the extent to which peer support values are maintained in practice. Given the diversity of peer support, the authors caution against prescriptive frameworks that might "codify" peer support and note that lived experience should be central to shaping and leading evaluation of peer support. Originality/value: This paper adds to the literature on peer support in mental health by describing a systematic approach to understanding how principles and values underpin peer worker roles in the context of mental health services. This paper informs an innovative, principles-based approach to developing a handbook and fidelity index for a randomised controlled trial. Lived experiences of mental distress brought to the research by members of the research team and the expert advisors shaped the way this research was undertaken.